The coffee ingredients caffeic acid and caffeic acid phenylethyl ester protect against irinotecan‐induced leukopenia and oxidative stress response. (16th July 2020) - Kalthoff, Sandra; Paulusch, Stefan; Rupp, Alexander; Holdenrieder, Stefan; Hartmann, Gunther; Strassburg, Christian P.
Abstract : Background and Purpose: Irinotecan, used in colorectal cancer therapy, is metabolized by glucuronidation involving different UDP‐glucuronosyltransferase (UGT)1A isoforms leading to facilitated elimination from the body. Individuals homozygous for the genetic variants UGT1A1*28 (Gilbert syndrome) and UGT1A7*3 are more susceptible to irinotecan side effects, severe diarrhoea and leukopenia. The aim of this study was to investigate the protective effects and active constituents of coffee during irinotecan therapy using humanized transgenic (htg) UGT1A ‐WT and htgUGT1A ‐SNP (carry UGT1A1*28 and UGT1A7*3 polymorphisms) mice. Experimental Approach: HtgUGT1A mice were pretreated with coffee or caffeic acid (CA) + caffeic acid phenylethyl ester (CAPE) and injected with irinotecan. The effects of coffee and CA + CAPE were investigated using reporter gene assays, immunoblot, TaqMan‐PCR, siRNA analyses and blood counts. Key Results: Only the combination of the two coffee ingredients, CA and CAPE, mediates protective effects of coffee in a model of irinotecan toxicity by activation of UGT1A genes. Coffee and CA + CAPE significantly increased UGT1A expression and activity along with SN‐38 glucuronide excretion in irinotecan‐injected htgUGT1A mice, resulting in significant improvement of leukopenia, intestinal oxidative stress and inflammation. Conclusion and Implications: In this study, we identify the compounds responsible for mediating the previously reported coffee‐induced activation of UGT1A gene expression. CA and CAPE represent key factors for the protective properties of coffee which are capable of reducing irinotecan toxicity, exerting antioxidant and protective effects. Provided that CA + CAPE do not affect irinotecan efficacy, they might represent a novel strategy for the treatment of irinotecan toxicity.